Recommendations on Chronic Constipation (Including Constipation Associated with Irritable Bowel Syndrome) Treatment - Pierre Paré; Ronald Bridges; Malcolm C Champion; Subhas C Ganguli; James R Gray; E Jan Irvine; Victor Plourde; Pierre Poitras; Geoffrey K Turnbull; Paul Moayyedi; Nigel Flook; Stephen M Collins (Canadian Journal of Gastroenterology)
While chronic constipation (CC) has a high prevalence in primary care, there are no existing treatment recommendations to guide health care professionals. To address this, a consensus group of 10 gastroenterologists was formed to develop treatment recommendations. Although constipation may occur as a result of organic disease, the present paper addresses only the management of primary CC or constipation associated with irritable bowel syndrome. The final consensus group was assembled and the recommendations were created following the exact process outlined by the Canadian Association of Gastroenterology for the following areas: epidemiology, quality of life and threshold for treatment; definitions and diagnostic criteria; lifestyle changes; bulking agents and stool softeners; osmotic agents; prokinetics; stimulant laxatives; suppositories; enemas; other drugs; biofeedback and behavioural approaches; surgery; and probiotics. A treatment algorithm was developed by the group for CC and constipation associated with irritable bowel syndrome. Where possible, an evidence-based approach and expert opinions were used to develop the statements in areas with insufficient evidence. The nature of the underlying pathophysiology for constipation is often unclear, and it can be tricky for physicians to decide on an appropriate treatment strategy for the individual patient. The myriad of treatment options available to Canadian physicians can be confusing; thus, the main aim of the recommendations and treatment algorithm is to optimize the approach in clinical care based on available evidence.